Response of Balanced Laminate Subjected to Abrupt Heat Flux: A New Perspective - Salih N. Akour (The Scientific World Journal)
A new perspective presents how the interaction between the material stiffness of both matrix and fibre took place to form the laminate response. Thin square simply supported balanced laminated composite plate of different ply arrangements subjected to abrupt heat flux is utilized in this investigation. The effect of ply arrangement on the elapse time for vibrations to vanish and the maximum response amplitude is also investigated. The finite element analysis results show that the response is an amplitude modulated signal that represents frequencies of both fibre and matrix. The analysis shows that the ratio of the carrier frequency to the modulating frequency matches the ratio of the fibre stiffness to ply lateral stiffness. Through the investigation, the maximum static deformation and the dynamic amplitude are illustrated for different ply arrangements. Furthermore, it is found that almost all laminates have a similar elapsed time for vibrations to vanish.